Validitas Pembayaran Kompensasi sebagai Pemenuhan Kewajiban Penyediaan Lahan Pemakaman dalam Perspektif Hans Kelsen - Singgih Wibisono; Gusti Yosi Andri (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The difference in regulations between the obligation to provide physical burial land and the compensation payment mechanism raises questions about the validity of the norms and the legal responsibility of the developer. This study aims to analyze the desynchronization of regulations on the provision of burial land and to examine the validity of compensation payments as a form of fulfilling the developer's obligations according to Hans Kelsen's perspective. This research is a doctrinal legal study focusing on the system of norms and legal rules governing the provision of burial land in housing development. The approach used is the legislative approach and the conceptual approach, utilizing primary and secondary legal materials, as well as interviews as supporting materials to clarify the results of the legal material review. The research results indicate a desynchronization of regulations between central and regional policies due to the expansion of the compensation mechanism from a specific instrument in lowincome housing to a generally applied instrument. The desynchronization is evident in the differences in regulations between the norm that emphasizes the physical provision of burial land and regional regulations that allow for a broader scope of compensation payments. Regulatory harmonization is carried out by reaffirming the provision of physical land as the primary obligation and integrating compensation payments with the cemetery land procurement system, recording, reporting and transparency in the realization of compensation fund usage. From the perspective of Hans Kelsen's theory, compensation payments retain validity and binding force as long as the norm governing them has not been revoked, thus not eliminating the developer's legal responsibility but rather transforming the form of its fulfillment into a reparative obligation.